The Effect of Nursing Round on Patient Satisfaction in Nursing Services - Azhari, Indah; Sukartini, Tintin (Fundamental and Management Nursing Journal, 2021)
Introduction: Implementing a nursing round has a positive impact on patient satisfaction. This method increase patient-nurse interaction and improve the quality of nursing care and patient satisfaction. The aimed of this study to conduct a literature review discusses the effect of nursing rounds on patient satisfaction in nursing services to enhance application knowledge (evidence-based) and optimal implementation.Method: This study used a literature review design, review articles or journals searched in three electronic databases (Scopus, ScienceDirect, and ProQuest). The Joanna Briggs Institute Critical Appraisal tools and Webb (2019) were used to assess the quality and Prism checklist as a review guide. Journal articles prospecting using the PICOS framework with inclusion criteria, the population is hospitalized patient who receive nursing services at the hospital and nurses who apply the nursing round, nursing intervention rounds, the outcome is patient satisfaction with nursing services, in English with a publication year between 2011-2020. The results of the search obtained 10 studies that match the inclusion criteria to be reviewed. Data tabulation and narrative analysis were performed on the articles or journals found.Results:  The results of this study show that the nursing round has advantages that affect patient satisfaction, some of the advantages provided are the resolved patients problems, the patient's needs can be fulfilled, raise up a professional nursing community, the establishment of cooperation between health workers, and nurses able to carry out apropriate and precise nursing care model.Conclusion: The implementation of the nursing round influences in  improving the quality of nursing care through the application of theoretical concepts to evidence-based nursing practice.